Walking Exercise as an alternative choice in lowering blood pressure in hypertensive patients: Systematic Review - Arum Dwi Ningsih (Bina Sehat Press. Departement Research and Community Engagement Bina Sehat PPNI Institute of Health Science, Indonesia, 2020)
Introduction: Hypertension is a condition, where someone has a blood pressure systole ≥ 140mmHg and a blood pressure diastole ≥ 90nmmHg. Hypertension is a health condition that affects 26% of people worldwide. The World Health Organization (WHO) in the